A Multifaceted Adaptive Algorithm-Based Framework for the Development of an University Student Knowledge Experiential Platform Focused on Creativity and Entrepreneurship - Dr. Munaga Ramakrishna Mohan Rao, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
To keep up with the advances in IT, the nation needs a robust pool of creative problem solvers and visionary business owners, and today's college students have the potential to become our country's most potent source of new ideas. Higher education institutions provide courses in Double creation, which boost students' general quality and marketability. We live in an Internet age, and we must use its potential to improve Double creative instruction. Currently, there is no information experience the system, analyses the data of the system builds a college student Double creation information experience system, and performs tests on the system to test its performance, on the student Double creation platform of colleges and universities. The experimental findings validate the accuracy and efficacy of the system data, demonstrating that the system data computed using the multi-dimensional dynamic algorithm is appropriate for the Double creative experience of college students